Self-Actualization in Anjana Bhattarai’s Jivankaa Ghumti ra Deuraliharu - Kattel, Achut Raj (Creative Vision: Multidisciplinary Journal of PMC, 2025)
Writing about the self in the form of nonfiction is a very popular genre in Nepali literature. Bhattarai’s Jivankaa Ghumtee ra Deuraliharu: A Collection of Travel Accounts and Memoirs presents her experiences of life in the form of nonfiction, mainly travelogue and memoir, and shows the gradual development of her personality. This research focuses on Bhattarai’s experiences and the process of building personality. It provides a lesson to readers and guides them to proceed ahead in the twists and turns of life successfully. It follows the humanistic approach of studying personality and applies Carl R. Rogers’ theory of actualizing self. It is qualitative research and adopts a textual analysis method by the technique of close reading of the text. The major findings of the present research are Bhattarai moves to self-actualization after learning the lesson of self-dependency from home. She learns that progress in the profession is the main goal of her life. She travels to various places in the nation and abroad and remembers the events from her childhood and compares her childhood memory with the events and the visited places in her professional life. She shows strength, aspiration to learn new things and fulfill the human potential and optimism in life. The study concludes that Bhattarai has an autonomous self and learns gradually from the very beginning of life how to maintain, actualize and enhance it and she began to learn about society and profession from the family and she began to believe in hard work. She liked to move forward in gaining knowledge, her profession and writing. The text can be explored from other theoretical aspects like feminism in the future.